PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN MINAT DAN KETERAMPILAN MENULIS TEKS EKSPLANASI - Gabriella Sophia Pinastiti; Andayani Andayani; Sumarwati Sumarwati (Universitas Sebelas Maret, 2020)
The aim of this study was to improve: the students’ interest and text writing skills towards the explanatory text for 8th-grade students of SMP Kristen Satya Wacana Salatiga by applying a problem-based learning model. This study is a classroom action research conducted in two cycles. Acctivities carried out in the implementation phase consist of five stages in accordance with the problem based learning, namely (1) problem orientation, (2) organizing students for investigation, (3) guiding investigation, (4) developing and presenting results, and (5) analyzing and evaluating promblem solving. According to the results of the analysis, the students’ interest toward explanatory texts is the first cycle was 50% or as many as 10 students, in the second cycle the students’ interest increased becoming 85% or as many as 17 students. While the results of explanatory text writing skills showed significant results. In the first cycle, the students’ interest in explanation text is 65% or as many as 13 students. Then, it increased in the second cycle which is 100% or all students have succeeded in achieving the minimum completeness criteria that have been determined previously, which is 75